Merkel cell polyomavirus-specific immune responses in patients with Merkel cell carcinoma receiving anti-PD-1 therapy. Issue 1 (27th November 2018) - Miller, Natalie J.; Church, Candice D.; Fling, Steven P.; Kulikauskas, Rima; Ramchurren, Nirasha; Shinohara, Michi M.; Kluger, Harriet M.; Bhatia, Shailender; Lundgren, Lisa; Cheever, Martin A.; Topalian, Suzanne L.; Nghiem, Paul
Abstract : Background: Merkel cell carcinoma (MCC) is an aggressive skin cancer that frequently responds to anti-PD-1 therapy. MCC is associated with sun exposure and, in 80% of cases, Merkel cell polyomavirus (MCPyV). MCPyV-specific T and B cell responses provide a unique opportunity to study cancer-specific immunity throughout PD-1 blockade therapy. Methods: Immune responses were assessed in patients ( n = 26) with advanced MCC receiving pembrolizumab. Peripheral blood mononuclear cells (PBMC) were collected at baseline and throughout treatment. MCPyV-oncoprotein antibodies were quantified and T cells were assessed for MCPyV-specificity via tetramer staining and/or cytokine secretion. Pre-treatment tumor biopsies were analyzed for T cell receptor clonality. Results: MCPyV oncoprotein antibodies were detectable in 15 of 17 (88%) of virus-positive MCC (VP-MCC) patients. Antibodies decreased in 10 of 11 (91%) patients with responding tumors. Virus-specific T cells decreased over time in patients who had a complete response, and increased in patients who had persistent disease. Tumors that were MCPyV(+) had a strikingly more clonal (less diverse) intratumoral TCR repertoire than virus-negative tumors ( p = 0.0001). Conclusions: Cancer-specific T and B cell responses generally track with disease burden during PD-1 blockade, in proportion to presence of antigen. Intratumoral TCR clonality was significantly greater in VP-MCC than VN-MCC tumors, suggesting expansion of a limited number of dominant clones in response to fewer immunogenic MCPyV antigens. In contrast, VN-MCC tumors had lower clonality, suggesting a diverse T cell response to numerous neoantigens. These findings reveal differences in tumor-specific immunity for VP-MCC and VN-MCC, both of which often respond to anti-PD-1 therapy.